The ER–PM interaction is essential for cytokinesis and recruits the actin cytoskeleton through the SCAR/WAVE complex - Zhijing Xu; Jingze Zang; Xintong Zhang; Qiwei Zheng; Yifan Li; Nadine Field; Jindriska Fiserova; Bing Hua; Xiaolu Qu; Verena Kriechbaumer; Michael J. Deeks; Patrick J. Hussey; et al. (Proceedings of the National Academy of Sciences, 2025)
Plant cytokinesis requires coordination between the actin cytoskeleton, microtubules, and membranes to guide division plane formation and cell plate expansion; how these regulatory factors are coordinated remains unknown. The actin cytoskeleton assembly is controlled by several actin nucleation factors, such as the SCAR/WAVE complex, which regulates actin nucleation and branching through the activation of the ARP2/3 complex. The activity of these actin regulatory proteins is likely influenced by interactions with specific membranes; however, the molecular basis and the biological relevance of SCAR–membrane interactions are also unclear. In this study, we demonstrate that the ER–PM tethering protein VAP27-1 directly interacts with SCAR2 at the ER membrane and that they colocalize to guide cell plate orientation during cell division. In the root meristem, both VAP27-1 and SCAR2 exhibit polarized localization at the cell plates, where the interaction between ER and PM is abundant. VAP27-1 recruits SCAR2 to the cell division plane, where there is a high concentration of actin filaments. In the vap27-1346 mutant, the densities of cortical ER, SCAR2, and consequently actin filaments are significantly reduced at the cell division plane, affecting cell plate orientation, cell division, and root development. A similar phenomenon is also observed in the scar1234 mutant, suggesting that VAP27 and SCAR proteins regulate cell division through a similar pathway. In conclusion, our data reveal a plant-specific function of VAP27-regulated ER–PM interaction and advance our understanding of plant ER–PM contact site and its role in cell division.